Respuestas

2014-01-24T20:22:28+01:00
5 x^{2} +15x-25=0 
 a=5; b= 15; c=-25

Sustituyendo en la resolvente
x= \frac{-b+- \sqrt{ b^{2}-4ac } }{2a}  [tex]x= \frac{-15+- \sqrt{ 225+500 } }{10}
x= \frac{-15+- \sqrt{ 5^{2}  }  \sqrt{29} }{10}  

x= \frac{-15+- 5 \sqrt{29}  }{10}

x= \frac{-3+- \sqrt{29} }{2}

Por lo tanto las respuestas son:
X1=(-3+√29)/2
X2=(-3-√29)/2







2014-01-24T20:26:50+01:00
 
5x^2 + 15x - 25 = 0 dividiendo todo por 5
x^2 + 3x - 5 = 0
factorizando
Usando la fórmula general
delta = b^2 - 4.a.c = (3)^2 - 4(1)(-5) = 29
x = [- b +/- (raiz delta)]/2a
x1 = [- 3 - (raiz 29)]/2
x2 = 
[- 3 + (raiz 29)]/2

                   S = { [- 3 - (raiz 29)]/2,  [- 3 + (raiz 29)]/2}